Anatomical research and clinical application of multistage advancement in dorsal finger V-Y flap - Qiu Shenqiang; Wang Zengtao; Chen Jingguo; Zhang Di; Sun Jun; Kou Wei; Hao Liwen; Xu Lanwei (Journal of Plastic Surgery and Hand Surgery)
Objective: To investigate the anatomical basis and clinical efficiency of the advancement distance in dorsal digital V-Y advancement flap.